2010
DOI: 10.1007/s11239-010-0519-8
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology, clinics and diagnostics of non-thrombotic pulmonary embolism

Abstract: Non-thrombotic pulmonary embolism (NTPE) is commonly defined as the partial or total occlusion of the pulmonary circulation caused by a variety of non-thrombotic embolic agents. Although its prevalence is much lower than that of pulmonary thromboembolism, this life-threatening pathology is often underestimated due to the low specificity of signs and symptoms and because it might be frequently overlooked in the differential diagnosis of the chest pain. The main sources of non-thrombotic pulmonary emboli include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 115 publications
0
26
0
10
Order By: Relevance
“…Likewise, deep vein thrombosis and the pulmonary embolisms that develop as a consequence are life-threatening complications following orthopedic surgeries and interventions [9]. Hyaluronic acid is one of the foreign materials accepted as an embolic [10]. Park et al reported a pulmonary embolism case after a cosmetic vaginal procedure with sodium hyaluronate injection.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, deep vein thrombosis and the pulmonary embolisms that develop as a consequence are life-threatening complications following orthopedic surgeries and interventions [9]. Hyaluronic acid is one of the foreign materials accepted as an embolic [10]. Park et al reported a pulmonary embolism case after a cosmetic vaginal procedure with sodium hyaluronate injection.…”
Section: Discussionmentioning
confidence: 99%
“…Диагностика нетромботической эмболии ЛА может быть сложной [464]. Эмболы небольших раз меров (микроэмболы) не видны при КТ легких.…”
Section: нетромботическая эмболизация лаunclassified
“…Under some circumstances, however, non-diagnostic values of D-dimer may be present in patients with DVT and/or PE, essentially when D-dimer is tested too early or too late after the development of VTE, after initiation of anticoagulant therapy, in patients with small and peripheral DVT [43]. Normal D-dimer values are also frequently found in patients with non-thrombotic PE [44].…”
Section: D-dimer and Venous Thromboembolismmentioning
confidence: 99%